2006
DOI: 10.1111/j.1365-2095.2006.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial or total replacement of fishmeal by solvent-extracted cottonseed meal in diets for juvenile rainbow trout (Oncorhynchus mykiss)

Abstract: The effect of solvent-extracted cottonseed meal (SCSM) as a partial or total replacement of fishmeal was studied in juvenile rainbow trout (Oncorhynchus mykiss). Six experimental diets SCSM0, SCSM25, SCSM50, SCSM75, SCSM75A and SCSMT, containing a gradient of SCSM 0, 152, 305, 465, 460 and 610 g kg )1 to replace 0, 112.5, 225, 337.5, 337.5 and 450 g kg )1 fishmeal protein were fed to triplicate groups (initial body weight of 39.2 ± 0.1 g) for 8 weeks. The diet SCSM75A was supplemented with lysine and methionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
58
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 19 publications
14
58
1
5
Order By: Relevance
“…Esses e outros resultados controversos mostram que a eficiência de utilização de fontes protéicas alternativas de origem vegetal pode mudar consideravelmente, de acordo com o tipo e a qualidade do farelo incorporado nas dietas. Provavelmente, a impossibilidade de utilização de maiores níveis de inclusão de fontes vegetais esteja relacionada à presença de fibra, fatores antinutricionais e baixa palatabilidade, que podem diminuir a ingestão e aproveitamento dos alimentos pelos peixes (LUO et al, 2006).…”
Section: Resultsunclassified
“…Esses e outros resultados controversos mostram que a eficiência de utilização de fontes protéicas alternativas de origem vegetal pode mudar consideravelmente, de acordo com o tipo e a qualidade do farelo incorporado nas dietas. Provavelmente, a impossibilidade de utilização de maiores níveis de inclusão de fontes vegetais esteja relacionada à presença de fibra, fatores antinutricionais e baixa palatabilidade, que podem diminuir a ingestão e aproveitamento dos alimentos pelos peixes (LUO et al, 2006).…”
Section: Resultsunclassified
“…O efeito deletério da inclusão de fontes vegetais sobre o crescimento dos animais pode estar relacionado à presença de fibra, fatores antinutricionais (remanescentes) e baixa palatabilidade, que podem diminuir a ingestão de alimento pelos peixes (Luo et al, 2006). Embora o perfil de aminoácidos das dietas tenha sido similar, as diferenças encontradas podem ter sido resultantes da diferente disponibilidade de aminoácidos entre os tratamentos.…”
Section: Resultsunclassified
“…Cheng and Hardy (2002) reported that cottonseed meal could be used at 10% inclusion rate in trout diets. According to Luo et al (2006), this level could be as high as 30%. On the contrary to these results, Gomes et al (1995) stated that plant protein sources like lupin seed meal, bean meal, pea seed meal, corn gluten, full-fat soybean and rape seed meal mixture could be utilized in rainbow trout diet up to 66%, to replace of FM.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the research for the substitution of FM in the diets of rainbow trout, numerous studies (Tacon et al, 1984;Hughes, 1991;Moyano et al, 1992;Pongmaneerat and Watanabe, 1992;Sanz et al, 1994;Morales et al, 1994;Gomes et al, 1995;Cheng and Hardy, 2002;Thiessen et al, 2003a;2003b;Luo et al, 2006) have shown that it is possible to partially or even fully replace FM by plant protein sources, such as soybean meal, sunflower meal, lupin flour, corn gluten meal, cottonseed meal, canola meal, rapeseed meal and so forth.…”
Section: Fındık Küspesi Seviyelerinin Gökkuşağı Alabalığı Yavrularındmentioning
confidence: 99%